Empowered Villages and the Paradox of Poverty Intervention Between Administrative Design and Social Transformation in West Nusa Tenggara - Habibullah Habibullah; Azwar Subandi; Lalu Sopan Tirta Kusuma (Visi Pencerah Nusantara, 2026)
This article examines the paradox of village-based poverty alleviation programs in West Nusa Tenggara (NTB), highlighting the tension between neat administrative designs and the need for profound social transformation. Building on reflections on the “Empowered Village” Program in NTB, this paper examines three main issues: (1) the limitations of expenditure-based poverty approaches, (2) the problem of direct assistance and thematic programs that are not accompanied by a change in mindset, and (3) the risk of administrative bias when poverty reduction targets are too pressing. The method used is a literature review with content analysis of studies on Empowered Villages, village economic empowerment, and poverty alleviation strategies in eastern Indonesia. The results of the study indicate that many programs are administratively successful (indicators achieved, reports are neat), but changes in economic culture, local institutions, and cultural poverty have not been truly touched (Orbawati et al., 2024; Lestary et al., 2022; Nisak ​​& Kusbandrijo, 2025; Toda, 2016). Studies on the Rumah Zakat Empowered Village (Desa Berdaya Rumah Zakat), the development of Village-Owned Enterprises (BUMDes), the creative economy, and local agribusiness show that a combination of mentoring, institutional strengthening, economic literacy, and citizen participation results in more sustainable transformation (Barung et al., 2025; Orbawati et al., 2024; Rosyidi et al., 2022; Savira et al., 2025). This article recommends strengthening the social change design within the NTB Empowered Village Program through a behavior change curriculum, more contextually relevant poverty mapping, and repositioning mentors as social learning facilitators rather than merely program administrators.